To Work or Not to Work? Child Development and Maternal Labor Supply - Sha, M; Frijters, P; Johnston, D.W; Shields, M.A (My University, 2009)
We estimate the effect of early child development on maternal labor force participation. Mothers of poorly developing children may remain at home to care for their children. Alternatively, mothers may enter the labor force to pay for additional educational and health resources. Which action dominates is the empirical question we answer in this paper. We control for the potential endogeneity of child development by using an instrumental variables approach, uniquely exploiting exogenous variation in child development associated with child handedness. We find that a one unit increase in poor child development decreases maternal labor force participation by approximately 10 percentage points.
American Economic Journal: Applied Economics
Keywords: Gender -- Female; Employment -- Labour force participation; Child Development; Childhood and child development; Gender; Labour market; Employment; Child Development; Gender; Female; Labour force participation; Employment and unemployment; Childhood and child development; Gender